(untitled) (American Journal of Arts and Human Science, 2025)
Russia’s growing involvement in Africa over the past two decades reflects a strategic push to expand its geopolitical, economic, and security influence on the continent. Drawing on historical ties from the Soviet era, Russia has positioned itself as a key partner for African nations, offering military assistance, counter-terrorism cooperation, and peacekeeping support. Key findings highlight Russia’s significant role as a leading arms supplier to Africa, accounting for nearly 40% of the continent’s arms imports between 2018 and 2022. Additionally, the deployment of private military contractors (PMCs), such as the Wagner Group, has become a hallmark of Russia’s security strategy, enabling it to project power while maintaining plausible deniability. The 2019 Russia-Africa Summit in Sochi marked a turning point, symbolizing Moscow’s commitment to deepening ties with Africa, resulting in numerous bilateral agreements and increased diplomatic engagement. Economically, Russia has focused on energy projects, such as nuclear power plants and gas collaborations, though its trade volume remains modest compared to other global powers. These efforts align with Russia’s broader strategy to counter Western influence, secure access to natural resources, and position itself as a reliable partner for African governments facing security challenges. This paper examines the evolution of Russia-Africa relations, focusing on security cooperation, and assesses its implications for regional stability and global geopolitics.